Non-Sinusoidal PWM Method for Cascaded Multilevel Inverter - Shahrin Md Ayob; Zaenal Salam; Abdul Halim M. Yatim (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
This paper presents a new switching method for Cascaded Multilevel Inverter (CMI).  The new method uses multiple non-sinusoidal signals as the modulating signal.  The main advantage of using non-sinusoidal modulating signal is that it provides higher fundamental component but at the cost of having a numbers of low-order harmonics in its unfiltered output voltage; naturally contributed by the non-sinusoidal modulating signal. In this paper, the Trapezoidal waveform is employed as the non-sinusoidal modulating signal for the CMI.  Its harmonics profile of different slope angles is analysed.  From the analysis, it was found that the trapezoidal with the slope angle of 36o eliminates the third and fifth harmonics yet yields a high fundamental magnitude.  To verify, a single-phase CMI prototype is constructed and an ALTERA FPGA is deployed to implement the proposed method’s algorithm.  From the results, it was shown that analysis is validated DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.855